Aggression and empathy in athletes - Hawkins, T. (Celebrating Scholarship and Creativity Day. 145, 2021)
This study investigated the relationship between aggression and empathy in those who play contact sports, non-contact sports, and those who are not athletes using previously developed measures. Three hypotheses were proposed: First, that there will be an inverse correlation between empathy and aggression regardless of sport. Second, that those who play contact sports will have lower scores on empathy and higher on aggression than those in non-contact or no sports. And third, that male participants will score higher on aggression and lower on empathy than female participants, regardless of sport involvement. After data analysis, it was found that hypothesis 1 was strongly supported; aggression and empathy measures had a strong negative correlation with an effect size of - 0.353. Hypothesis 3 was also supported by moderately significant data showing a difference in aggression between males (mean = 2.712) and females (mean = 2.439) with an effect size of d = 0.456. Empathy levels were found to be very significantly different between males (mean = 42.0) and females (mean = 48.273) with an effect size of d = 1.012. Hypothesis 2 regarding different types of athletes and their aggression and empathy levels received low levels of support and more research and specificity is required to fully determine differences in this area of comparison.